Presenting the Development Model of Active Sports Tourism with an Economic Approach: the Share of Health-Oriented Sports in the Gross Domestic Product - Zahra Sohrabi; Mehrdad Moharam Zadeh; Rasool Nazari (Sports Business Journal)
Purpose: More comprehensive and practical research is needed on active sports tourism, the importance of sports development in Iran, and its impact on the economy. Therefore, the current study aims to develop a sports tourism development model with an economic approach to address various aspects of increasing sports tourism's share in the gross domestic product.Methodology: This qualitative study used the database theory strategy and Charms's constructivist approach. Data were collected using in-depth semi-structured interviews. Nineteen experts in three fields—sports science, economy, and tourism—participated in the research.Findings: The interviews' 210 sentences were implemented into 145 initial and 22 focused codes. Finally, the factors identified from the interviews were classified into six core categories: health-giving movements, institutionalization, active lifestyle, health, people and society, and economy. The current model acknowledges that active sports tourism may directly and indirectly affect the Gross domestic product (GDP).Originality: It was found that increasing attention to active sports tourism improves people's health and quality of life and can also lead to increased productivity, reduced health costs, the growth of related industries, and an increase in gross domestic product.